2015
DOI: 10.1590/s0102-053620150000100012
|View full text |Cite
|
Sign up to set email alerts
|

Sistema Viçosa para o cultivo de tomateiro

Abstract: A adequação de práticas culturais como tutoramento, condução de plantas e densidade de plantio, é importante para a qualidade e aparência dos frutos de tomate, agregando valor e consequentemente maior lucratividade (Marin et al., 2005; Shiraige et al., 2010).O tutoramento e a condução de plantas podem maximizar a captação da radiação solar e a ventilação ao longo do dossel, influenciando na umidade relativa e a disponibilização de gás carbônico atmosférico às plantas (Wamser et al., 2008).Cerca cruzada ou "V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
2
9
0
6
Order By: Relevance
“…The market demand for fresh tomatoes with enhanced taste and cooking versatility has expanded the cultivation of saladette/roma tomato plants ( Shirahige et al, 2010 ). However, high production costs, along with the strong susceptibility of the crop to various types of biotic and abiotic stresses have driven the search for alternative, more feasible growth varieties for producers ( Wamser et al, 2012 , Almeida et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The market demand for fresh tomatoes with enhanced taste and cooking versatility has expanded the cultivation of saladette/roma tomato plants ( Shirahige et al, 2010 ). However, high production costs, along with the strong susceptibility of the crop to various types of biotic and abiotic stresses have driven the search for alternative, more feasible growth varieties for producers ( Wamser et al, 2012 , Almeida et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2013), evaluating the fertigation of tomatoes in a protected environment, observed that the excessive fertilization caused a reduction in the number of fruits obtained per plant. Likewise, Almeida et al (2015), evaluating conduction systems, observed a yield ranging from 48.22 t ha -1 (10,000 plants per hectare) and 109.58 t ha -1 (25,000 plants per hectare), thus demonstrating that there is a great variation in yields between different cultivation systems for the tomato culture.…”
Section: Discussionmentioning
confidence: 96%
“…The difference in yields, comparing the Distrito Federal regions with other Brazilian regions, could be related to the tomato cultivation during the winter, in addition to different types of plant conduction systems (Melo and Vilela 2005). Almeida et al (2015), analyzing agronomic characteristics in the cultivation of hybrid tomatoes, in different conduction systems, obtained an estimated yield of 74.65 t ha -1 for tomato plants grown with just one stem. In this study, tomato plants grown with only one stem showed a higher estimated yield, 106 t ha -1 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Viçosa cultivation system and its adaptations provided promising results and are very well accepted in the horticultural community for providing greater insulation and aeration to plants. Moreover, it markedly reduces the incidence of phytopathogens in the culture, which is crucial in reducing the volume of pesticides applied to tomato crops, and the problems of their residual effect, while providing greater productivity and profitability (Almeida et al, 2015).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%